The Spanish version of the Brief Young Adult Alcohol Consequences Questionnaire (B-YAACQ): A Rasch Model analysis - Pilatti, Angelina (2014)
The present work was aimed at analyzing the psychometric properties of the Spanish Brief YAACQ in a sample of Argentinean college students applying the Item Response Theory. Participants were 302 college students (59.9% females) who reported drinking alcohol within the last month. The B-YAACQ was translated into Spanish and the psychometric properties of this Spanish version were analyzed applying the Rasch Model, as well as testing group difference and conducting correlational analyses. The verification of the global fit of the data showed adequate indexes for the persons and items. The reliability estimate of the items was very high (.97), while the reliability estimate of the persons was modest (.65). All but one item had adequate fit indexes. B-YAACQ scores were strongly related to measures of hazardous alcohol drinking, including frequency of drunkenness episodes and frequency of heavy episodic drinking, indicating concurrent validity. The item content along the severity continuum was fairly similar to that found with US and Dutch samples. Three items had a gender bias against men and another three items showed a gender bias against women, indicating the presence of differential item functioning cancelation. The map of items and persons suggests that these 24 items do not provide a full coverage of the continuum of alcohol problems at the lower levels of the continuum. Overall, results from the present study suggest that the Spanish B-YAACQ offers a brief and efficient way to identify alcohol problems in Spanish-speaking college students.